2006
DOI: 10.1029/2005gl025569
|View full text |Cite
|
Sign up to set email alerts
|

Riverine influence on nitrogen fixation in the upwelling region off Vietnam, South China Sea

Abstract: [1] Nitrogen fixation is assumed to be most important in oligotrophic subtropical regions of the oceans. Here we show that nitrogen fixation can also be pronounced in the upwelling region off Vietnam. We compare nitrogen fixation rates and other hydro-chemical variables from the monsoon season with the intermonsoon season and find that nitrogen fixation rates are app. 10 times higher during the monsoon season. However, this was not the case in the actual upwelling region -a 40-50 km wide strip along the coastb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
91
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(111 citation statements)
references
References 20 publications
16
91
1
3
Order By: Relevance
“…Previously, it was estimated that N 2 fixation provides up to 10% of the total carbon production in the SCS (Voss et al, 2006;Loick et al, 2007). The highest potential for N 2 fixation was suggested to occur during the summer monsoon with no contribution during spring intermonsoon .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it was estimated that N 2 fixation provides up to 10% of the total carbon production in the SCS (Voss et al, 2006;Loick et al, 2007). The highest potential for N 2 fixation was suggested to occur during the summer monsoon with no contribution during spring intermonsoon .…”
Section: Discussionmentioning
confidence: 99%
“…The central gyre is permanently stratified and oligotrophic, and N limitation of phytoplankton growth has been reported (Wu et al, 2003), suggesting that the environment is favorable for nitrogen (N 2 ) fixation. Rate measurements suggest that production based on N 2 fixation contributes approximately 10% of total production, with the highest rates measured during the monsoon seasons in winter and summer and the lowest rates during intermonsoon (Voss et al, 2006). Bloom-forming filamentous N 2 -fixing cyanobacterium Trichodesmium spp.…”
Section: Introductionmentioning
confidence: 99%
“…This figure is higher than is found in other parts of the SCS (Grosse et al 2010). Furthermore, nitrogen fixation rates measured in the upwelling region off Vietnam showed an approximately 10-fold increase during the monsoon season compared with the inter monsoon season (Voss et al 2006). Factors mentioned above have increased the heterogeneity of the distribution of diazotrophs in this area.…”
mentioning
confidence: 60%
“…Later it was also shown that in the SCS, N 2 fixation occurs at very high and ecologically significant rates in surface waters affected by Mekong River outflow (Voss et al 2006) ( Table 2). By combining approaches to study hydrography and nutrient setting in the Mekong River plume, we can now provide a clearer picture of how environmental factors determine phytoplankton species selection and lead to enhanced N 2 fixation.…”
Section: Discussionmentioning
confidence: 95%